Eosinophils in Eosinophilic Esophagitis: The Road to Fibrostenosis is Paved With Good Intentions - Doyle, Alfred D.; Masuda, Mia Y.; Kita, Hirohito; Wright, Benjamin L. (Frontiers in Immunology, 2020)
Eosinophilic esophagitis (EoE) is an antigen-driven disease associated with epithelial barrier dysfunction and chronic type 2 inflammation. Eosinophils are the defining feature of EoE histopathology but relatively little is known about their role in disease onset and progression. Classically defined as destructive, end-stage effector cells, eosinophils (a resident leukocyte in most of the GI tract) are increasingly understood to play roles in local immunity, tissue homeostasis, remodeling, and repair. Indeed, asymptomatic esophageal eosinophilia is observed in IgE-mediated food allergy. Interestingly, EoE is a potential complication of oral immunotherapy (OIT) for food allergy. However, we recently found that patients with peanut allergy may have asymptomatic esophageal eosinophilia at baseline and that peanut OIT induces transient esophageal eosinophilia in most subjects. This is seemingly at odds with multiple studies which have shown that EoE disease severity correlates with tissue eosinophilia. Herein, we review the potential role of eosinophils in EoE at different stages of disease pathogenesis. Based on current literature we suggest the following: (1) eosinophils are recruited to the esophagus as a homeostatic response to epithelial barrier disruption; (2) eosinophils mediate barrier-protective activities including local antibody production, mucus production and epithelial turnover; and (3) when type II inflammation persists, eosinophils promote fibrosis.